Ductal Carcinoma-in-situ Arising within Fibroadenoma of the Breast: A Case Report, Mammographic, Sonographic and Dynamic Contrast-enhanced Breast MRI Features - Gonthong, Ananya (Journal of The Department of Medical Services, 2021)
A 38-year-old woman was diagnosed with invasive ductal carcinoma in the left breast status, following left modified radical mastectomy and chemotherapy lasting 1 year. She had undergone annual surveillance mammography and ultrasonography. Mammography revealed developed fine pleomorphic calcification within the mass and correlated Color Doppler study demonstrated internal vascularity. Core needle biopsy was done and pathological report of ductal carcinoma in situ with fibroadenoma. Pre-operative MRI was obtained. Finally, pathological diagnosis after right simple mastectomy revealed ductal carcinoma in situ arising in fibroademona, that is rare disease.